Impact of a Patient Navigation Program on Cancer Treatment in Kenya - Shahid Umar; Andriy Chybisov; Erica Krisel; Hayley Freedman; Catherine Nyongesa; Anastacia Bosire; Sitna Mwanzi; Anurag K. Agrawal; Kristie McComb (JCO Global Oncology)
PURPOSEPatient navigation (PN) is a critical intervention in the United States to overcome barriers to cancer care, including logistical, financial, and informational barriers, ensuring patients receive timely and coordinated care. However, there are few studies assessing effectiveness of PN in low- and middle-income countries (LMICs). Here, we aim to begin to fill this gap by assessing the effectiveness of the Kenyatta National Hospital (KNH) patient navigation program (PNP) in improving patient-reported outcomes (PROs).MATERIALS AND METHODSWe used repeated cross-sectional survey design by collecting data from randomly selected 1,126 adults with cancer in three surveys conducted in 2018, 2019, and 2022. The study also drew on qualitative data collected from patients with cancer, caregivers, and program team members as part of an external outcome evaluation.RESULTSLogistic regression showed that a higher number of navigation encounters was associated with increased likelihood of improving patients' understanding of their diagnosis, duration of treatment, and satisfaction with information received about needed clinical services. Compared with the 2018 survey, participants of the 2019 (odds ratio [OR], 12.00, 8.00-17.99) and 2022 (OR, 17.18, 10.88-27.14) surveys had markedly higher odds of receiving help finding their way around the facility. Moreover, compared with the 2018 survey, participants of the 2019 survey had lower odds of delaying the start or continuation of their treatment (OR, 0.50, 0.32-0.78).CONCLUSIONThis study contributes to a limited pool of studies to assess PROs of PNPs specifically for cancer treatment in LMICs, making an important contribution to the existing body of knowledge in global cancer patient support. This study provides evidence that PNPs can function effectively and complementarily in LMICs.